Marilyn's monster - Knudsen, Michelle (Candlewick Press, 2015)
A lot of Marilyn's friends have monsters. It's the latest thing. Each one is just right for its boy or girl. Marilyn really wants a monster, too, but despite her efforts to be the kind of girl no monster could resist, hers just doesn't come. What could be taking it so long? Everyone knows you just have to wait for your monster - but the spunky and determined Marilyn thinks there may be other ways that things can work
Keywords: Monsters / Juvenile fiction; Friendship / Juvenile fiction; Monsters / Fiction; Friendship / Fiction; Friendship; Monsters; Bilderbuch